Strategy Towards a Uniform Civil Code - lyer, V R Krishna (Journal of Dharma, 1986)
I realize the importance of the theme which is being discussed today : a uniform civil code in a multi-religious society. The discussion of a subject which is merely abstract may be carried on in an intellectual atmosphere. But when the subject becomes emotional and the parties involved or affected get into paroxysm, I wonder whether intellectual clarity or even political sanity can be preserved. Unfortunately this subject has already kindled feelings and emotions among various sections of the people : the Hindus who constitute a preponderant majority in this country, the Muslims, the most substantial minority, the Christians, the Jains and the Buddhists, the Zoroastrians or the Parsees, each important, however small numerically the minority may be. And the Sikhs whose number gives no indication of their capabilitie